First results of ADVANCE Study: clinical practice value - S. V. Nedogoda (Кардиоваскулярная терапия и профилактика, 2008)
The ADVANCE Study, started in early 2001, included 11140 patients aged over 55 years, with Type 2 diabetes mellitus (DM-2) and one more risk factor (RF): age 65 years and above, macro- or microvascular pathology in anamnesis, DM-2 duration over 10 years, etc. In patients with DM-2 and arterial hypertension (AH), blood pressure control could be achieved with perindopril + indapamide combination (4,0/1,25 mg), regardless of clinical and demographical parameters. Long-term combination therapy (4,5 years) was associated with substantial decrease in cardiovascular risk among DM-2 individuals, regardless of AH presence or absence and treatment characteristics.